Effects of Salt Stress on Plant Growth, Antioxidant Capacity, Glandular Trichome Density, and Volatile Exudates of Schizonepeta tenuifolia Briq. - Zhou, Ying (Int J Mol Sci, 2018)
Salinity is a major abiotic factor affecting plant growth and secondary metabolism. However, no information is available about its effects on Schizonepeta tenuifolia Briq., a traditional Chinese herb. Here, we investigated the changes of plant growth, antioxidant capacity, glandular trichome density, and volatile exudates of S. tenuifolia exposed to salt stress (0, 25, 50, 75, 100 mM NaCl). Results showed that its dry biomass was reduced by salt treatments except 25 mM NaCl. Contents of antioxidants, including phenolics and flavonoids, increased at low (25 mM) or moderate (50 mM) levels, but declined at severe (75 and 100 mM) levels. On leaf surfaces, big peltate and small capitate glandular trichomes (GTs) were found. Salt treatments, especially at moderate and severe concentrations, enhanced the density of total GTs on both leaf sides. The most abundant compound in GT volatile exudates was pulegone. Under salinity, relative contents of this component and other monoterpenes decreased significantly; biosynthesis and accumulation of esters were enhanced, particularly sulfurous acid,2-ethylhexyl hexyl ester, which became the second major compound as salinity increased. In conclusion, salt stress significantly influenced the growth and secondary metabolism of S. tenuifolia, enabling us to study the changes of its pharmacological activities.